Needs assessment for cultural adaptation of Strengthening Families Program (SFP 10-14-UK) in Brazil - Murta, Sheila Giardini (Psicol Reflex Crit, 2018)
This study sought to evaluate the cultural adequacy of materials and procedures of the Strengthening Families Program (SFP 10-14-UK) and to identify requirements for its cultural adaptation to Brazilian families. The descriptive study had 33 informants, including external observers, managers, multipliers, facilitators, adolescents, and parents. The data were collected at a pilot application in the Federal District. Direct observation was applied to four intervention groups, with seven meetings of 150 min for families, parents/guardians and adolescents, and mixed nominal groups at the end of the interventions. The results, analyzed through content analysis and descriptive statistics, provided evidence that SFP was perceived as sufficiently appealing, culturally relevant, and partially clear. Recommendations for cultural adaptation of linguistic aspects of the materials and procedures were made, considering the cultural and educational differences of the participant families. Focus on implementation quality, including infrastructure, families’ mobilization and continuous planning, was recommended. Replication studies in other Brazilian regions and analyses of contextual and political dimensions are suggested.